Accidental Overdosing in Patients with Take-Home Methadone – A Case Series - Anshul Sharma; Sidharth Arya; Gunjan Chadha; Rajiv Gupta (Annals of Indian Psychiatry)
Methadone maintenance therapy is administered at designated centers in India as “daily observed treatment” regimen. During the COVID-19 pandemic, guidelines were relaxed, and take-home methadone was allowed for 5–7 days. We discuss three cases of accidental methadone overdose among the patients who were on take-home dispensing. Among three cases, overdose was experienced by the patient himself in one case, while in the second one, it was by 2-year-old child of the patient, and in the third one, by the patient’s wife which proved fatal. Increasing number of treatment centers is likely to take up take-home policies owing to the ease and comfort of the patients. There is an urgent need to develop interventions which can be useful in supervising take-home dispensing and reducing the potential overdosing incidents.